The Conceptions of Sharia and Citizenship in Indonesia and Malaysia - Muhamad Ali (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2019)
Indonesia and Malaysia offer comparative perspectives concerning the relationship between loyalties to the Muslim umma, local ethnicity, and the modern nation-state, and how interpretations of the sharia and modern constitution, laws, politics, and policies intersect in multiple and changing ways. This article seeks to compare and contrast some of the contemporary discourses on sharia and citizenship as demonstrated by Indonesian and Malaysian scholars, politicians, and activists. Both Indonesian and Malaysian constitutions were born out of the modern notion of citizenship that recognizes religious diversity. On the one hand, the Constitution of Indonesia does not specify Islam as the state religion, but the government promotes official religions. On the other hand, the Constitution of Malaysia makes it explicit that Islam is the state religion while recognizing religious diversity. The Indonesian government does not conflate particular ethnicity with Islam, whereas Malaysia integrates Islam and Malay ethnicity amidst Malaysian religious and ethnic plurality. Both cases prevent us from categorizing each case as either an Islamic legal conservatism or a modern legal liberalism. These two cases resist the binary opposition between sharia conservatism deemed against citizenship and modern legal liberalism deemed against religious laws. There are ambiguities, contradictions, as well as compromises and integration between conflicting ideas and systems concerning Islam and citizenship.